The Performance of the Foreign Exchange Markets: 1971–1974 - Kohlhagen, Steven W. (Journal of International Business Studies, 1975)
This paper explores the behavior of the foreign exchange markets for the floating rate period since 1973 and the immediately preceding fixed rate period. The author presents evidence showing that the cost of forward cover and the gains from speculation in the forward market for the major currencies has not changed significantly between the two periods and, in fact, the forward rate has been an unbiased predictor of the future spot rate for the floating rate period.